Post-flutter response of a flexible cantilever plate in low subsonic flows. (May 2017) - Chen, Tao; Xu, Min; Xie, Dan; An, Xiaomin
Abstract: Numerical simulations on the post-flutter response of a flexible cantilever plate are carried out by establishing a nonlinear aeroelastic model. The present study shows that chaotic movements may exist in the three-dimensional panel flutter problems in case of low subsonic flows. In the analysis, time traces, phase-plane plots, Poincare maps as well as power spectral densities are employed to identify the dynamic behavior of the system. It is observed that the plate undergoes period-1, period-3 and non-periodic motions with the increase of inflow velocity. The post-flutter behavior is dominated by both geometric and aerodynamic nonlinearities. Numerical results show that wingtip vortexes are in fact an important source of aerodynamic nonlinearities, which have not been fully studied before. The study also provides a criterion on how to choose a coupling strategy in the nonlinear aeroelastic simulation of a low-aspect-ratio flexible structure in low subsonic flows when the dominant nonlinear effect is different in the post-flutter response. Abstract : Highlights: An aeroelastic model considering the strong coupling of geometric and aerodynamic nonlinearities is established. Chaotic movements are likely exist in low subsonic three dimensional panel flutter problems. Wing tip vortex will cause significant nonlinear effects on the post flutter responses. The impact of coupling strategy depends on the strength of geometric and aerodynamic nonlinearities.